Establishing a new appropriate intramuscular injection site in the deltoid muscle - Yukari Nakajima; Kanae Mukai; Kana Takaoka; Toshiko Hirose; Keiko Morishita; Takuya Yamamoto; Yuka Yoshida; Tamae Urai; Toshio Nakatani (Taylor & Francis Group, 2017)
It is becoming increasingly important for clinicians to identify a safer intramuscular (IM) injection site in the deltoid muscle because of possible complications following the vaccine administration of IM injections. We herein examined 4 original IM sites located on the perpendicular line through the mid-acromion to establish a safer IM injection site. Thirty healthy volunteers participated in this study and the distances from our 4 IM sites to some anatomical landmarks on their left arms were measured. Ultrasonography (US) was also performed to measure the thickness of the deltoid muscle and identify the posterior circumflex humeral artery (PCHA) along the course of the axillary nerve. Subcutaneous thickness was measured using 2 methods: measuring the skin thickness with caliper after pinching the skin, and with US. The results obtained revealed that the intersection between the anteroposterior axillary line (the line between the upper end of the anterior axillary line and the upper end of the posterior axillary line) and the perpendicular line from the mid-acromion was the most appropriate site for IM injections because it was distant from the axillary nerve, PCHA, and subdeltoid/subacromial brusa. At this site, depth of needle insertions was 5 mm greater than the subcutaneous thickness at a 90° angle, which was sufficient to penetrate subcutaneous tissue in both sexes. Subcutaneous thickness can be assessed with almost the same accuracy by US or measuring with calipers after pinching the skin. The results of the present study support the improved vaccine practice for safer IM injections.